Concept of body in Jose Watanabe’s poetry. Hermeneutics of doctor-patient relationship - Li Ning Anticona, José Luis (2012)
The following study correlates three poems of Jose Watanabe (1946-2007) -“El Ojo”, “Mi Casa”, and “Como el Peje-sapo”- with the existentialist notion of the body. Three bodies are delimited, a biologic, conscious, and a cultural one, in order to facilitate the phenomenological description of doctor-patient relationship.